Natural History of Early Onset Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The clinical course of multiple sclerosis (MS) in 116 patients with onset before age 16 (prevalence 3.6% in total MS clinic attendees) was evaluated by longitudinal study (mean duration 19.76 +/- 0.9 years) at the University of British Columbia MS Clinic.